Mosaic of Drosophila Behavior Due to Bisphenol-A Exposure: From Hyperactivity to Aversion - Fauzi, Ahmad; Ramadhan, Muhamad Justitia; Kharomah, Sindi; Kharomah, Sinta; Zahrah, Natasya Adiba; Setiawan, Deny; Buroidah, Hikmah; Bilad, Muhammad Roil; Zubaidah, Siti (Universitas Negeri Semarang, 2025)
Bisphenol-A (BPA) is classified as an endocrine-disrupting chemical that is widely found in everyday food. However, various studies have reported inconsistent results regarding the effects of this exposure on behavior. This study aimed to evaluate how dose, genetic background, and duration of exposure interact to shape behavioral responses in Drosophila melanogaster exposed to BPA. Three strains (Wild-type, white-eye, and black-body) were cultured on a medium containing 0, 0.25, and 0.5 mg/mL BPA for two generations. Before exposure (G0), after the first generation of exposure (G1), and after the second generation of exposure (G2), three behaviors were measured: larval crawling speed, number of larval contractions, and larval exploration distance. Repeated-measures ANOVA revealed a non-monotonic pattern in behavioral responses. Each behavior exhibited distinct sensitivities to treatment factors, and complex interactions were observed between genetic factors, dose, and time (generation). Furthermore, the effects of BPA are not general but rather specific to the type of behavior observed. Generational effects are evident in some behavioral data. In addition, fly strain plays a role in determining the effect of exposure on behavioral responses.